DEVELOPMENT OF MICROCAPSULES BASED ON COMBINED ANTIDIABETIC SUBSTANCE: PHARMACOLOGICAL CHARACTERISTICS - A. Giyoszoda; E. F. Stepanova; O. F. Veselova; S. E. Storozhenko (Volgograd State Medical University, Pyatigorsk Medical and Pharmaceutical Institute, 2022)
The comparative assessment results of the hypoglycemic activity of a combined preparation containing microcapsules with a phytocomposition consisting of Glycyrrhiza glabra L. extracts, a dry extract of Galega officinalis L., Mentha piperita L., and gliclazide, are discussed in the article. Methods for obtaining microcapsules with an original PEG-6000 shell are described.The aim of the study was to develop an optimal technology for obtaining microcapsules with a PEG-6000 shell containing a combined antidiabetic substance, and conduct its detailed pharmacological study on the model of type 2 diabetes mellitus, to conduct a detailed comparative pharmacological study of a microencapsulated antidiabetic composition with a shell based on PEG-6000, including gliclazide and a sum of phytoextracts on the model of type 2 diabetes mellitus.Materials and methods. As the main objects of the study, microcapsules with a PEG-6000 shell were obtained using methyl miristate as the base liquid. The capsules contained the amount of plant extracts in their composition: a dry extract of Glycyrrhiza glabra L., a dry extract of Galega officinalis L., a dry extract of Mentha piperita L., and gliclazide. The study of a hypoglycemic activity was carried out after a single administration of drugs to the animals with alloxan-induced type 2 diabetes mellitus. The cumulative effect assessment of the drugs was carried out within 14 days with a test for the resistance to oral glucose on days 7 and 14.Results. Microcapsules with the original shell were obtained by dispersion in a liquid-liquid system with the adjustment of some technological stages. The effect of the drugs under study on the glycemic profile in the rats with an experimental model of type 2 diabetes mellitus was investigated. A comparative evaluation of the pharmacological effect was carried out with a separate and combined use of microencapsulated preparations.Conclusion. The rationality of combining phytocomponents and a synthetic antidiabetic agent in microcapsules has been proven. The obtained results testify to the rationality of plant extracts combination and a synthetic hypoglycemic agent - gliclazide in microcapsules.